1560 Cerbe Deni̇z Savaşi - Köse, Sevilay (The Journal of Social Sciences, 2025)
Djerba Island, which had been a refuge for famous pirates since the second half of the 16th century, had an important position for the Mediterranean. Especially when Turgut Pasha, the Beylerbeyi of Tripolitania, took Djerba Island under his control, the Christian world's interest in the island increased. The Crusader troops formed to capture Djerba managed to capture the island and built a castle on the island despite the disagreement between the commanders, bad weather conditions, epidemics and deserters. Upon this news, the Ottoman navy under the command of Piyale Pasha moved towards the island of Djerba. The Ottoman fleet, which was outnumbered, defeated the Crusader fleet off the coast of Djerba. While some of the Crusaders fled, some of them took refuge in the castle of Djerba. The Crusaders were besieged by sea and land for two months. The Ottoman navy forced the Crusaders to surrender by attacking the wells in the castle. In return for the surrender of the Crusaders, their lives were spared and the island of Djerba was annexed to Tripolitania under the Ottoman Empire. This study focuses on the conquest of Djerba by the Ottoman navy, which was an important centre of refuge for Turkish pirates and the domination of the Central Mediterranean.
Keywords: Djerba – Empire ottoman; Invasions chrétiennes – Djerba – 1560

Toward a Maghribi Turn in Ottoman History - Marglin, Jessica M.; Ismail, Youssef Ben (Journal of the Ottoman and Turkish Studies Association, 2024)
, ABSTRACT:, The fields of Ottoman and Maghribi history have largely developed independently of one another. Thanks to the outlooks of both colonialist and nationalist historiographies of the Maghrib, historians of North Africa for a long time mostly ignored the Ottoman presence or depicted the Ottomans as distant, foreign conquerors. Ottoman historians tended to see the Maghrib as peripheral to the history of the empire and to portray North African provinces as largely irrelevant to the core of Ottoman history. Since the 1970s, a smattering of scholars has attempted to connect the histories of the Ottoman Empire and the Maghrib. Building on this growing body of work, this article argues for the usefulness of taking the Ottoman Empire seriously in the study of Maghribi history, and of taking the Maghrib seriously in the study of the Ottoman Empire. After an exploration of the historiography, we turn to a discussion of sovereignty as an example of what the Maghribi turn in Ottoman history might look like. Rather than consign North Africa to an imagined periphery, we ask how Ottoman historiography can be reimagined when we view the empire from the Maghrib.
Keywords: Djerba – Empire ottoman

An Ibadi Diplomat in late-Ottoman Cairo: The Life & Afterlife of Saʿid al-Shammakhi - Love Jr, Paul M. (Journal of the Ottoman and Turkish Studies Association, 2024)
, ABSTRACT:, This article follows the career of Saʿīd al-Shammākhī (d.1883), who served in Cairo, Egypt as the wakil of the Bey of Tunis from 1871–1881. I suggest that Shammakhi's life and career as wakil offers novel valence and voice to an increasingly polyvalent, polyphonic, and polychronic history of late Ottoman North Africa; namely, that of an Ibadi Muslim commercial and diplomatic agent, whose career linked two late-Ottoman Arab provinces at a decisive period in their history. The article situates Shammakhi in recent scholarship on late-Ottoman North Africa, with an emphasis on work that has sought to decenter European imperialism and colonialism as the defining factors in the chronology and history of the region. It also outlines his biography leading up to his appointment as wakil before then contextualizing Shammakhi's role as wakil by explaining the nature of that office. Shammakhi's time as wakil—and even the years following his death—expressed multiple belongings, imagined alternative futures past, and embodied a life and afterlife disrupted, but not defined, by the encounter between European imperialism and Ottoman lands in Africa.
Keywords: Biographies – Djerba – 19e siècle; Commerce – Djerba; Djerba – Empire ottoman

الصراع بين اتراك طرابلس وأتراك تونس حول جزيرة جربة وانعكاساته - بن غازي, البشير (2024)
Keywords: Djerba – Empire ottoman

الكتابة الإباضية بتونس والأزمنة التاريخية عند سعيد بن تعاريت المتوفي في سنة 1289ه/1872م - المريمي, محمد (2024)
Keywords: Djerba – Empire ottoman; Sources – Djerba

المصادر التاريخية وإستعمالاتها في علاقة الأقليات بالغيرية في البلاد التونسية - المريمي, محمد (مجلة أسطور للدراسات التاريخية, 2020)
Number: 011
Keywords: Djerba – Empire ottoman; Sources – Djerba

جزيرة جربة المحلي والمركزي: خلال العصر الحديث - المريمي, محمد (اباديكا, 2022)
Keywords: Djerba – Empire ottoman; Ibadisme – Djerba